Pengaruh Pijat Refleksi Terhadap Penurunan Nyeri Haid Pada Wanita Di Panti Yatim Putri Daerah Klaten Tahun 2016 - Paryono Paryono; Dwi Retna Prihati (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract : Reflexology, Decreased Menstrual Pain. The purpose of this study was to determine the effect of reflexology massage on the decrease of menstrual pain (Dysmenorrhea) in women at the Aisyiyah Putri Orphanage Klaten District. The design used in this research is the experiment with the design of Time series design. The sampling technique used Cluster sampling approach. Samples taken on women who have menstrual and experienced menstrual pain (disminore) as many as 30 people. conclusions Menstrual pain (desminore) was felt before reflexology in women at the 2016 Women's Orphanage at Klaten Region was classified as mild disturbing pain (scale 3.4 measured through Visual Analog Scale). Menstrual pain (desminore) was felt after a reflexology treatment in women at the Putri Panti Putri Klaten Tahun 2016 was classified as a mild pain (1.63 scale measured through Visual Analog Scale)